Improving Students’ Argumentation Style Ability in Writing Essay through Discourse Analysis Model Critical Thinking Map Oriented - R. Panca Pertiwi Hidayati (JETL (Journal of Education, Teaching and Learning), 2017)
Students’ ability in writing anessay, as one of language skills which can improve the creativity in language, is a serious problem that should be investigated by a deep research. Besides for showing that language as a thinking tool, writing competence can be seen as a product if we take a look from critical thinking ability measurement aspect and also as a process if we take a look at the individual development itself aspect. One of indicator for measuring the students’ critical is by the ability in delivering their argumentation style which is showed in their essay. The goal of this research is obtaining the objective discourse analysis model critical thinking map oriented in improving students’ argumentation style skills in writing anessay, hence can be used as a modelling for the growing of students’ creativity in a variety of writing skills. Based on paired-samples t test, the pre-test/post-test paired-sample is significant, because the significance (2-tailed) is less than 0.05 in the standard of 95%. This is mean, there is a real difference between the ability before and after getting the treatment. The sample’s ability after getting the treatment is better than before. As well as if be compared with control class, experiment class shows the significant superiority for all aspects of essay writing assessment.